Factors Affecting Retailers Attitude towards Manufacturers: A Study on Unilever - Alam, Muhammad Intisar (Journal of Economics and Behavioral Studies, 2011)
The study addresses broadly the performance related issues as to what extent is the impact of various factors responsible in terms of retailers for doing business with manufacturers in FMCG (Fast Moving Consumer Goods) sector at Dhaka in Bangladesh. The theoretical framework was designed based on the literature and hence two hypotheses were formulated. The samples were selected by Proportionate Stratified Sampling method. The data were collected by distributing 10 items questionnaires to 50 retailers under different categories in Dhaka. The questionnaire was developed on the basis of exploratory research which were used to measure retailers attitude. Data collected were sorted out and keyed in into SPSS and were analyzed using descriptive statistics to answer the research question. Using the Factor analysis we have extracted four factors and named those factors as Manufacturer’s Production Standard, Managerial Efficiency, Promotional Capability and Customer Solution Capability. The result of the Multiple Regression analysis showed that there is a significant relationship between retailers’ attitude (dependent variable) and the factors determined in the factor analysis (independent variables). Together the independent variables explained 67.9% of the variance of the dependable variables whereas the remaining 32.1% was due to unidentified variables. Therefore the results of the study definitely play a vital role and leave an ever lasting impact to be used in decision making by retailers and the entire company as a whole. Moreover this study can be used as a reference for the future studies to understand the perceptions and opinions of the other channel members in addition to retailers as well.